Identify Self-Efficacy and Self-Intention on The Impact of Preventing Covid 19 - Florentianus Tat; Maria Yoani Vivi Aty; Elisabeth Herwanti; Rohana Mochsen; Rafael Paun (Postgraduate, University of Mataram, 2023)
Corona virus disease 2019 is still developing with various new variants. Protection of health workers from the risk of infection is very important. Preventing the transmission of Covid-19 to health workers while carrying out their duties starts from themselves through a good work culture, self-efficacy and commitment to health protocols that have been established by the government. The research objective is to identify the relationship between self-efficacy and self-intention of health workers in sustainable prevention of Covid-19 in NTT. The quantitative research method uses a cross sectional study design, the population of health center health workers is 2233 people with a sample of 300 people. The research results showed that there was an influence of work culture on Covid 19 prevention behavior (p=0.001). Self-efficacy influences Covid-19 prevention behavior and self-intention influences Covid-19 prevention behavior in health workers. The conclusion is that work culture, self-efficacy and self-intention (intention) influence the Covid 19 prevention behavior of health workers. Suggestions for variables that influence Covid 19 prevention behavior to receive attention from the government